The Effect of Conversion of Extradition Methods and Unlawful Deportation on Human Rights in Nigeria - Antai, Godswill Owoche; Ndifon, Cyril Osim; Ikubanni, Oluwaseye Oluwayomi; Ogba, Sylvester Adejoh; Imiefoh , Andrew Ikhayere (CV. Pustaka Parawali, 2025)
This study examines how the practices of secret extradition and illegal deportation violate human rights protection in Nigeria, and in particular, how such violations weaken constitutional privilege and international normative principles. The objective of this study is to examine the legal and human rights implications, particularly in situations where individuals are transferred across borders without due process or judicial supervision. Using a doctrinal research approach that is complemented by a review of national laws and extra-territorial policies, the study uses both the example of the rendition of Nnamdi Kanu and an attempted kidnapping of Umaru Dikko, among others, to argue that there appears to be a trend towards state-execution-led extra-territorial enforcement practices. The study shows that such clandestine operations often contravene the most basic rights, such as the right to a fair trial, protection against torture and the right to liberty and security of the person. The study further demonstrates an enduring conflict between the Nigerian state's interest in national security at all costs and a statutory and human right commitment under domestic and international law. The research holds that the lack of transparency, absence of legal guarantees and failure to comply with established extradition processes are undermining the rule of law and creating dangerous precedents of impunity. It calls for legislative and legal overhauls combined with enhanced judicial supervision, and respect for due process as necessary steps to herald in national security considerations in tandem with Nigeria’s human rights obligations.